Intracranial Arterial Aneurysms - J Gordon Millichap (Pediatric Neurology Briefs)
Neurosurgeons from the Universita degli Studi di Roma “La Saspeinza,” Rome, Italy, report a 4-year-old girl with a cerebral saccular aneurysm and analyze 71 cases under 5 years of age in the literature.